2008
DOI: 10.1016/j.genhosppsych.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of race in diagnostic and disposition decision making in a pediatric psychiatric emergency service

Abstract: Objective-We investigated the influence of race/ethnicity in diagnostic and disposition decisionmaking for children and adolescents presenting to an urban psychiatric emergency service (PES).Method-Medical records were reviewed for 2991 child and adolescent African American, Hispanic/Latino, and White patients, treated in an urban PES between October 2001 and September 2002. A series of bivariate and binomial logistic regression analyses were employed to delineate the role of race in the patterns and correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 46 publications
(51 reference statements)
0
21
0
Order By: Relevance
“…Blacks with a SUD had higher odds of being diagnosed with CD, impulse-control, and psychotic diagnoses, while whites with a SUD had higher odds of AD, ADHD, MD, PD, relational, and eating diagnoses. Data from other treatment-seeking samples also show a higher prevalence of disruptive behavioral and psychotic disorders but a lower prevalence of internalizing disorders, PD, and ADHD among blacks compared with whites (McGilloway et al, 2010; Muroff et al, 2008; Stevens et al, 2005). …”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Blacks with a SUD had higher odds of being diagnosed with CD, impulse-control, and psychotic diagnoses, while whites with a SUD had higher odds of AD, ADHD, MD, PD, relational, and eating diagnoses. Data from other treatment-seeking samples also show a higher prevalence of disruptive behavioral and psychotic disorders but a lower prevalence of internalizing disorders, PD, and ADHD among blacks compared with whites (McGilloway et al, 2010; Muroff et al, 2008; Stevens et al, 2005). …”
Section: Discussionmentioning
confidence: 87%
“…Rates of comorbidities by race/ethnicity, however, are infrequently reported (Armstrong and Costello, 2002; O'Neil et al, 2011). Available data suggest that black children or adolescents with a psychiatric disorder are more likely than their white counterparts to receive inpatient psychiatric treatment and be diagnosed with disruptive behavioral or psychotic disorders, while whites are more likely to be diagnosed with internalizing disorders and SUDs (Muroff et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…African American youth are shown to be more frequently diagnosed by their clinicians with conduct disorder and psychotic disorders and less often diagnosed with mood, anxiety, adjustment, and substance abuse disorders (Fabrega, Ulrich, & Mezzich, 1993; Kilgus, Pumariega, & Cuffe, 1995; Mak & Rosenblatt, 2002), however it is unclear about whether they were actually more seriously ill at the time of the referral. Similarly, in psychiatric inpatient settings, African American male adolescents were more frequently diagnosed with schizophrenic spectrum disorders while non-Hispanic White adolescents were more often diagnosed with alcohol abuse, major depression, and bipolar disorder (Delbello, Lopez-Larson, Soutullo, & Strakwoski, 2001; Muroff, Edelsohn, Joe, & Ford, 2008; Patel, Delbello, & Strakowski, 2006; Tolmac & Hodes, 2004). Mandell, Ittenbach, Levy, and Pinto-Martin (2007) found a delay in diagnosis of autism for African American children as they were less likely than White children to receive an autism diagnosis at their first specialty care visit.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Hispanic adolescents (age 13–17 years) had fewer psychiatric disorder diagnoses overall than any of the other ethnic groups (Leal, 2005). Hispanic adolescents presenting at emergency services were more likely to receive diagnoses of psychotic or behavioral disorders than non-Hispanic White adolescents (Muroff et al, 2008), although it is possible that they were more ill before presenting to emergency services. In a state-wide publicly funded service system, minority children (which included Hispanic children) were 38% more likely to receive diagnoses of oppositional defiant disorder compared to non-Hispanic White children, after controlling for other variables such as age and gender (Heflinger & Humphreys, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Muroff et al [44] reported that race/ethnicity are independently associated with certain mental health diagnoses. A review of 2991 visits to an urban pediatric psychiatric emergency service showed that black and Hispanic children were more likely to receive a psychotic disorder or a behavioral disorder diagnosis compared with white children.…”
Section: Mental Healthmentioning
confidence: 99%